The kinetics of tempeh wastewater treatment using Arthrospira platensis - Lieke Riadi; Theresia Desy Askitosari; Ragil Puspita Dutaning Widhi; Melvina Laurensia; Yuana Elly Agustin; Yalun Arifin (Water Science and Technology, 2021)
The microalga Arthrospira platensis (Spirulina) was used for tempeh wastewater treatment. Microalga growth and the kinetics of chemical oxygen demand (COD) degradation under different light intensities (2,100 and 4,300 lux), tempeh wastewater concentrations (0, 0.5, 1, 1.5% v/v), and sodium nitrate concentrations (0, 0.75, 1, 2, 2.5 g/L) were studied. Improved cell growth in wastewater indicated that mixotrophic growth was preferred. The addition of sodium nitrate up to 2 g/L increased COD removal. The highest COD removal was 92.2%, which was obtained from cultivation with 1% v/v tempeh wastewater, 2 g/L sodium nitrate, 2,100 lux, and the specific growth rate of 0.33 ± 0.01 day−1. The COD removal followed a pseudo-first-order kinetic model with the kinetic constant of 0.3748 day−1 and the nitrate uptake rate of 0.122 g/L-day. The results can be used to design a pilot-scale tempeh wastewater treatment facility using A. platensis for tertiary treatment. Based on the kinetic model, a 20 m3 reactor can treat tempeh wastewater to reduce the COD from 400 to 100 ppm in 4 days and produces approximately 32.8 kg of dried microalgae. HIGHLIGHTS The alga Arthrospira platensis can reduce COD value in diluted tempeh wastewater up to 90% COD removal.; The addition of sodium nitrate up to 2 g/L improves the COD reduction.; The COD degradation follows a pseudo-first-order kinetic model.; The results can be used to design a pilot-scale tempeh wastewater treatment facility using A. platensis for tertiary treatment.;